CHANGES OF PHYSICAL PROPERTIES OF THE MESH GILLNET IN THE RIVER WATERS OF PULAU JAMBU VILLAGE KUOK DISTRICT KAMPAR REGENCY RIAU PROVINCE - Sri Ayu Anggraini; Alit Hindri Yani; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted in April 2018 in the river waters of Plau Jambu Village Kuok District Kampar Regency Riau Province. In the implementation of this study the data collected aims to determine changes in the physical properties of gillnet with different ages, namely 0 months, 3 months, 6 months, 12 months, as well as to obtain technical age in gillnets in river waters Pulau Jambu Village Kuok District Kampar Regency Riau Province. The research begins with samping in the field, then continued measurements (Breaking load, mesh elongation, and node stability), and analysis at the Fishing Equipment Material Laboratory of Department of Fisheries Resource Utilization, Faculty of Fisheries and Marine Affairs, University of Riau. The Results of this study indicate that the breaking load on the mesh experienced a decrease with time, this can be see by the BP equation (Breaking load) = -0,0592x + 0,686. In the value of elongation also decreased with the equation of KM (Mesh elongation) = -0,479x + 14,34. Whereas for node stability there is no node shift because the net breaks at the foot of the thread instead of the loose node. Based on this study it can be concluded that the technical age of the net is 12 months. Keywords: Mesh size, gillnet, physical properties, usage age, technical age